GIANT MAGNETORESONANCE EFFECT OF NiFe/Ag/ NiFe MULTILAYERS PREPARED WITH DC SPUTTERING TECHNIQUE ON Ag DEPOSITION TIME - Mohammad Toifur; Kamsul Abraha; . Ridwan (Universitas Ahmad Dahlan, 2009)
A study on the Giant Magnetoresonance (GMR) effect of NiFe/Ag/NiFe multilayers on Ag deposition time (tAg) ranging from 1 to 3 minutes has been performed. The study was intended to obtain the most suitable Ag deposition time to give the largest GMR ratio by using 150 G deposition field in transverse direction of anode-chathde and C substrate temperature during deposition. Several characterizations have been performed including morphological sample cross section, microstructure, magnetic properties of the layer, and GMR ratio in an external magnetic field ranging from -20 up to 20 gauss. The results show that multilayers with tag = 2 minutes displays the largest GMR ratio of 54.87%. The layer has a high level of atomic structure ordering, a large grain size, the highest remanence and the smallest coercive power. The situation is close to Pool’s estimation that the GMR ratio for trilayers of approximately 50%.